Zambrano, Pilar - Saunders, William L. (Coords.), Unborn Human Life and Fundamental Rights: Leading Constitutional Cases Under Scrutiny, Peter Lang GmbH, 2019, 264 pages - Kiska, Roger (2019)
Fil: Kiska, Roger. Christian Legal Center; Reino Unido